Gambaran tingkat kepercayaan diri mahasiswa profesi dalam melakukan perawatan gigi tiruan lengkap (Laporan Penelitian) - Siti Azizah; Yenny Pragustine (Fakultas Kedokteran Gigi Universitas Trisakti, 2022)
Background: Dentists need to undergo professional education by performing dental care on patients supervised by lecturers. The aim of complete denture treatment is to restore mastication function, aesthetic and phonetic function. In the complete dentures treatment, the dental profession students must feel confident on behalf of the patient’s health and convenience, because if it is not based on the right method, it will cause tissue damage inside and outside the oral cavity. Objectives: To observe the confidence level of dental students at Faculty of Dentistry, Universitas Trisakti in carrying out complete denture treatment. Methods: This research is an observational descriptive study with a cross-sectional study design to describe the confidence level of dental students in carrying out complete denture treatment. Results: Based on the results of the study, respondents were dominated by female respondents, and based on age categories, respondents were dominated at the age of 22 years. The confidence level based on gender, the median value of female students confidence is 58 while for male students is 57.5 Conclusion: The confidence level based on gender characteristics showed that female respondents had a greater score compared to male respondents.